Atypical Language Development in Romance Languages - Eva Aguilar-Mediavilla; Lucía Buil-Legaz; Raúl López-Penadés; Victor A. Sanchez-Azanza; Daniel Adrover-Roig (John Benjamins Publishing Company, 2019)
This book presents a range of ongoing studies on atypical language development in Romance languages. Despite the steady increase in the number of studies on typical language development, there is still little research about atypical language development, especially in Romance languages. This book covers four main conditions causing atypical language development. Part I explores the linguistic and communicative characteristics of preterm children learning Romance languages. The focus of Part II centers on children with Specific Language Impairment. Hearing Loss in Part III is another relevant factor leading to atypical language development. The final part IV zeroes in on genetic syndromes coupled to cognitive impairment with special attention to language development. This book presents a much needed overview of the most recent findings in all relevant fields dealing with atypical language development in children speaking Romance languages.